A Novel Approach to Blockchain for Financial Transactions in Rural Sectors - Abisha, S; Chitra, K. (INTI International University, 2025)
Rural communities often remain excluded from formal financial systems due to weak infrastructure, limited digital access, and high dependence on intermediaries. Traditional blockchain systems, while efficient in urban and global contexts, are not directly suited to these conditions because of their high transaction costs and reliance on constant internet connectivity. This paper proposes a novel blockchain-based framework designed specifically for rural economies. The approach emphasizes affordability, inclusivity, and offline functionality, while ensuring security and scalability. Transactions are made accessible through USSD/SMS on feature phones, verified with community-supported digital credentials, and processed on lightweight permissioned blockchains using local edge nodes. Pilot simulation results highlight substantial benefits: transaction times reduced from days to seconds, costs lowered by over 60%, and greater community trust through transparent local governance. This study offers a sustainable pathway for extending financial inclusion to underserved rural populations through an offline first, community-governed blockchain system.